Sosiodemografi dan tingkat kecemasan mahasiswa pada masa pandemi COVID-19 - Virliana Aulia Intan; Rizky Muharany Putri; Hoirun Nisa (Jurnal Psikologi Sosial, 2022)
The COVID-19 pandemic is an epidemiological crisis. It has impacted psychological conditions, creating concerns about the mental health of young people around the world – including anxiety issues. Though past research has revealed that the level of anxiety may depend on the person's sociodemographic background, not many have examined the topic within the pan-demic context. Moreover, sociodemographic context may differ – due to cultural relativism. This study aimed to determine the relationship of sociodemographic factors with anxiety levels in university students. This study used a cross-sectional study design. Participants were undergraduate students of UIN Syarif Hidayatullah. The accidental sampling method was used to select 415 participants. Data collection was performed online using a google form. Data were analyzed by univariate, bivariate, and multivariate tests. The results of this study showed that the prevalence of severe anxiety was 57.20% (n=239) in university students. The results of multivariate analysis showed that relatives/acquaintances affected by COVID-19 and geographic location were associated with anxiety levels (p<0.05). Participants who have relatives/acquaintances infected with COVID-19 have a 1.70 times higher risk of experiencing severe anxiety (OR=1.70; 95%CI=1.111-2.602). Participants who live in urban areas have a 1.79 times higher risk of experiencing severe anxiety (OR=1.79; 95%CI=1.142-2.818). Students were expected to manage anxiety during a pandemic. Recommendation to the university includes providing health promotions to prevent the transmission of COVID-19 and psychological consultation services to maintain the mental health of students during the pandemic.